Depression, Harassment and Gender as Determinants of Absenteeism - Yacob, Zahra Giovana; Asri, Cahya Purnama; Bahri, Bahri; Sari, Utami Tunjung; Artha, Bhenu (Multidisciplinary Journal of Education , Economic and Culture, 2026)
Absenteeism has emerged as a critical indicator of individual well-being and institutional effectiveness, particularly within educational and organizational settings. Defined as the habitual non-attendance at work or school without valid justification, absenteeism reflects deeper psychosocial and structural issues that merit rigorous investigation. This research uses theoretical review to analysis connection between depression, harassment, gender, and absenteeism. This research presents that depression, harassment, and gender significantly influence absenteeism through complex interconnected mechanisms. Absenteeism should be recognized as an aspect related to performance